Monitoring of sandflies (Diptera: Psychodidae) and pathogen screening in Slovenia with habitat suitability modeling - Ivović, Vladimir; Glasnović, Peter; Zupan, Sara; Knapič, Tea; Trilar, Tomi; Korva, Miša; Knap, Nataša; Glinšek Biškup, Urška; Avšič-Županc, Tatjana; Adam, Katja (Frontiers in Veterinary Science, 2025)
Sandflies (Diptera: Psychodidae: Phlebotominae) are important vectors of pathogens, including Leishmania parasites and phleboviruses, but their distribution and seasonal activity in Slovenia have not been sufficiently studied. This study presents a comprehensive three-year (2020–2022) surveillance programme aimed at assessing the diversity of sandfly species, their distribution, seasonal dynamics and potential role as vectors of pathogens. A total of 1,240 sandflies were collected at 43 sampling sites across Slovenia, identifying Phlebotomus papatasi, P. neglectus, P. perniciosus and P. mascittii. The highest abundance and species diversity were observed in the Mediterranean and Karst regions. Seasonal activity peaked in July, with population fluctuations influenced by climatic conditions. Molecular analyses for Leishmania parasites and phleboviruses showed no positive results, indicating a low prevalence of pathogens in the sampled populations. Predictive habitat models indicate that environmental factors, particularly temperature and precipitation, play a decisive role in the spread of sandflies. While P. mascittii has the largest ecological range, its vector competence remains uncertain. The results provide important insights into the ecology of sandflies in Slovenia and emphasize the need for continuous surveillance in the context of climate change and emerging vector-borne disease risks.